Challenges for the adoption of evidence-based maternity care in Turkey - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Evidence-based medicine is an important tool for improving the quality of maternity care. However, getting providers to change their practices may not be an easy or rapid process, and other factors, in addition to knowledge of the literature, may be important. This study documents the current state of obstetric practices at three maternity hospitals in Istanbul, Turkey, and identifies attitudes, social pressures, and perceptions that, according to the theory of planned behavior, may pose challenges for adoption of evidence-based practices. Data were collected through interviews with administrators, examination of hospital statistics, provider and client interviews, and structured observations of maternity care. Practices that did not follow current guidelines included routine episiotomy, not allowing companionship during labor, use of procedures to speed up labor without indications, routine enema, restriction of mobility, restriction of oral fluids, supine position for delivery, and non-use of active management of the third stage of labor. The findings indicate that providers had negative attitudes about some recommended practices, while they had positive attitudes towards some ineffective and/or harmful practices. We identified social pressure to comply with practices recommended by supervisors and peers, as well as the belief that limited resources affect maternity care providers, opportunities to perform evidence-based procedures. An underlying problem was the failure to involve women in decision-making regarding their own maternity care. In addition to informing providers about the evidence, it seems necessary to develop standard protocols, improve physical conditions, and implement behavior interventions that take into account provider attitudes, social pressures, and beliefs. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: evidence-based practice; theory of planned behavior; maternity care; Turkey; QUALITY-OF-CARE; LABOR